The stability of vocational interests from early adolescence to middle adulthood a quantitative review of longitudinal studies. [article]. - Juhasz, B.
The present meta-analysis examined the stability of vocational interests from early adolescence (age 12) to middle adulthood (age 40). Stability was represented by rank-order and profile correlations. Interest stability remained unchanged during much of adolescence and increased dramatically during the college years (age 18-21.9), where it remained for the next 2 decades. Analyses of potential moderators showed that retest time interval was negatively related to interest stability and that rank-order stability was less stable than profile stability. Although cohort standings did not moderate stability, interests of the 1940s birth cohort were less stable than those of other cohorts. Furthermore, interests reflecting hands-on physical activities and self-expressive/artistic activities were more stable than scientific, social, enterprising, and clerical interests. Vocational interests showed substantial continuity over time, as evidenced by their higher longitudinal stability when compared with rank-order stability of personality traits. The findings are discussed in the context of psychosocial development. -- (from the author)